Kedudukan dan Urgensi Shigat Taklik Talak Perspektif Ketentuan KHI Dan Hukum Fiqh Klasik: ANALISIS WACANA KRITIS ANTI-TESIS - Harahap, Rahmad Ibrahim; Siregar, Ramadhan Syahmedi (Tasyri' : Journal of Islamic Law, 2022)
That it is a habit among Indonesian Muslims when the consent procession is completed between the guardian of the prospective wife and the prospective husband, the husband will be asked by Tuan Kadhi (KUA marriage registrar) to read and/or pledge shigat taklik talak in front of him and witnessed by the the parties who participated in the procession of the marriage contract were the guardians of the prospective wife, the witness of the marriage and the other invited guests. This research is a type of qualitative research with a library database, and data analysis techniques with 3 approaches, namely the legal approach (read: statute approach), and conceptual approach (read; conceptual approach) and comparative approach (read: comparative approach). The conclusion of this paper is that there are several aspects of disharmony between the provisions of the Compilation of Islamic Law (KHI) and classical fiqh law and regarding the legal consequences of taklik talak which are violated by the husband in the future. The disharmony revolves around the status of the fall of divorce and the position of taklik talak as talak or iwadh'. Given that the rules of shigat taklik talak in the perspective of Islamic fiqh have significant differences with the rules of KHI, so there is a need for an in-depth analysis to look at this issue comprehensively with the aim of having an academic dialectic that provides a good understanding